BLOG AS ALTERNATIF MEDIA IN TEACHING LITERATURE - Y. Satinem (Bandar Lampung University (UBL), 2016)
The aims of this research are: 1) to know the students’ respond in utilization of blog as media in learning at students grade 3 Xaverius elementary school; 2) The effectiveness teaching folk lore by using blog at students grade 3 SD Xverius Lubuklinggau. Weblog or blog is one of interesting media used by teacher and students as teaching and learning media. Blog can be called as private website which in managing can be do individual or group. In this research, the researcher used quantitative method that focused at quasi-experimental research. Quantitative methods emphasize objective measurements and the statistical, mathematical, or numerical analysis of data collected through polls, questionnaires, and surveys, or by manipulating pre-existing statistical data using computational techniques. Quantitative research focuses on gathering numerical data and generalizing it across groups of people or to explain a particular phenomenon. In this research, researchers took xavarius elementary school as population and grade three as many as 31 students have been selected as samples for research. The result at this research were 1. The percentage of students’ answer who stated that learning literature by using media blog was approved, its means that blog media is necessary for learning. From 31 students who fill the questionnaire, show all students stated that the question number 7, 8 , and 10 are beneficial for students with a percentage of each question 100 % . From the students ‘statement can be concluded that learning by using media blog is required by Indonesian students on the material, especially regional literature. 2. Calculations to determine the effectiveness of media blogs in teaching regional literature is done by using the t test. From the results of calculations using SPSS result that t is greater than t table or in critical areas, Ho was rejected, meaning that the process of learning the Indonesian language by using the media blog on learning folklore applied to the third grade students of Xavarius elementary school had proved effective.